Factors influencing the acceptance of medical AI chat assistants among healthcare professionals and patients: a survey-based study in China - Zhang, Lanshan; Yang, Jingyi; Fang, Gege (Frontiers in Public Health, 2025)
IntroductionThis study examines the drivers behind healthcare professionals’ and patients’ acceptance of medical AI chat assistants in China.MethodsA nationwide online survey was conducted from March 10 to April 28, 2024, using quota sampling to collect 500 valid responses, and data were analyzed via structural equation modeling.ResultsPerformance expectancy, perceived cost, digital access, and digital competence all positively predicted intention to use, whereas patient age and consultation frequency—rather than socioeconomic status—directly influenced actual usage behavior.DiscussionFindings validate an extended UTAUT model in digital-health contexts, highlight cultural moderators of technology acceptance, and inform age-friendly AI design and equitable health-informatization policies in aging societies.